A Rare Cause of Abdominal Pain: Superior Mesenteric Artery Branch Pseudoaneurysm Rupture - Li, Qianqian; Gao, Yanhong; Yan, Hao; Qi, Xingshun; Ye, Chun (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Li Q, Gao Y, Yan H, Ye C, Qi X. A rare cause of abdominal pain: superior mesenteric artery branch pseudoaneurysm rupture. Turk J Gastroenterol. 2024;35(11):869-871.